Carcinogenicity Evaluation of Baclofen in TgrasH2 Mice. (January 2022) - Chevalier, Guillaume; Aubert, Nicolas; Thirion-Delalande, Catherine; Palate, Bernard; Singh, Pramila
Baclofen is a γ-aminobutyric acid-B receptor agonist used for control of spastic muscle activity and as a treatment for alcohol abuse. The review of the nonclinical database suggested a data gap for potential carcinogenicity following long-term use. Regulatory requirements for pharmaceutical safety testing of cancer-causing potential have historically included 2-year rodent studies in rats and mice. The availability of transgenic models with greater specificity and sensitivity to carcinogens provides safety testing alternatives that align with the 3Rs. The carcinogenicity of baclofen was evaluated in CB6F1-TgrasH2 transgenic mice following daily oral administration at 45, 90, and 180 mg/kg/d for 26 weeks, preceded by a 2-week drug-conditioning period. There were no treatment-related palpable masses or neoplastic findings, and survival rates were not affected by the baclofen treatment. In conclusion, baclofen was considered as noncarcinogenic in CB6F1-TgrasH2 mice, which is consistent with results previously obtained in a 2-year rat study.